The Double-Cross System - Masterman, J. C. 1891-1977 (New York Avon Books, 1972)
The amazing true story of how British intelligence penetrated and practically operated Nazi Germany's spy network within the British Isles.
Includes Tables, Appendix and Index.
Keywords: Secret Service -- World War (1939-1945) -- Great Britain